Жастарды салауатты өмір сүруге қалыптастыруда педагогикалық мәселделер - Ахметчина, Т.А.; Оразымбетова, Б.Б. (My University, 2013)
The youth of the future of our society. The upbringing of a healthy lifestyle among young people is the main pedagogical problem. The concept of a healthy way of life is much wider, than the absence of harmful habits, it also includes a system of relations to him, to another person, to life in General, as well as the meaning of life, life goals and values.